THE ANALYSIS OF ELEMENTARY TEACHER EDUCATION DEPARTMENT OF STAIN GAJAH PUTIH STUDENTS’ ENGLISH PROFICIENCY - Sungkawati Kardi Wahyuningsih (Jurnal As-Salam, 2017)
The aim of this research study is to describe the elementary teacher education department of STAIN Gajah Putih students’ English proficiency. The proficiency was in reading, writing, speaking, andlistening. The subjects of this study are 65 students of the elementary teacher education department students in the academic year 2015/2016. The research instrument was in the form of English proficiency test. The test consists of reading, listening, writing, and speaking tests. The quantitative data were obtained from the students’ answer sheet. The descriptive statistic was used to analyze the quantitative data. The results of the study are as follow. 41.75% of the students were in the level of knowledge. It was followed by comprehension with 28.75% of the students, application with 16.75% of the students, analysis with 8.5% of the students, synthesis with 3.75% of the students, and evaluation with 0.5% of the students.